Efforts to Increase the Self-Confidence of SMP Negeri 1 Tegaldlimo Students with Cognitive Behavior Counseling Guidebooks Modeling Techniques - Syabaruddin Dalimunthe; Putu Ari Dharmayanti; Kadek Ari Dwiarwati (Bisma The Journal of Counseling, 2023)
The low self-confidence possessed by students is indicated by the attitude of students who are not confident in expressing their opinions in front of the class. The low level of self-confidence then impacts decreasing student learning outcomes. One of the efforts that can be made to overcome this problem is to provide cognitive behavior guidance services to students. This research aims to develop and test the acceptability of cognitive behavior counseling guidebooks for modeling techniques to increase students' self-confidence. This research belongs to the development research type developed using a 4-D model. The subjects involved in this study were three counseling guidance lecturers as Ali, two counseling guidance teachers as practitioners, and seven junior high school students who were used as subjects in a limited trial. Data collection in the study was carried out using the questionnaire method, with the research instrument as a guidebook product validity instrument. The data obtained in the study were then analyzed using quantitative descriptive analysis techniques. The research analysis results show that the t-test obtained a probability score or Sig. (2-tailed) of 0.00, this probability score is smaller than the significance level of 0.05, which means H0 is rejected. Based on these results, it can be concluded that the cognitive behavior counseling guide is in the valid category, so it is effective for increasing student self-confidence.